Prehospital Paramedic Interventions In Road Traffic Accidents: A Systematic Review Of Outcomes And Survival Rates (The Review of Diabetic Studies, 2025)
Road traffic accidents (RTAs) remain one of the leading causes of injury and death globally, particularly in low- and middle-income countries. Prehospital paramedic interventions play a crucial role in reducing morbidity and mortality by stabilizing trauma patients and ensuring timely transport to appropriate facilities. This systematic review analyzes evidence from 2015–2025 regarding the effectiveness of paramedic-led interventions in improving survival rates and patient outcomes following RTAs. Databases including PubMed, Scopus, and Web of Science were searched for randomized trials, observational studies, and meta-analyses addressing airway management, hemorrhage control, spinal immobilization, fluid resuscitation, and rapid transport systems. Findings indicate that early intervention by trained paramedics significantly reduces prehospital mortality, shortens scene-to-hospital time, and improves neurological recovery in severe trauma cases. The review highlights the need for standardized trauma protocols, continuous professional training, and technology-enabled communication between paramedics and trauma centers. Future research should focus on AI-assisted triage, simulation-based training, and region-specific outcome measurement, particularly within developing healthcare systems.